Theoretical study on heat transfer characteristics of single screw refrigeration compressor with Multicolumn envelope meshing pair. (5th February 2020) - Wang, Zengli; Wang, Hao; Wang, Zongming; Li, Qiang; Feng, Quanke
Highlights: Theoretical model of heat transfer process for SSC with MEMP was established. Experiment study was put forward to verify the theoretical model. Heat transfer characteristics of the SSRC with MEMP were analyzed. Optimization analysis of the operating parameters was obtained. Abstract: In single screw refrigeration compressor (SSRC), the heat transfer has always been a key issue that affects its performance. However, the theoretical research on heat transfer characteristics of SSRC with Multicolumn Envelope Meshing Pair (MEMP) has not been carried out yet. Therefore, in this paper, a geometric model of heat transfer area and a theoretical calculation model describing the heat transfer process of the SSRC with MEMP are established to predict the heat transfer characteristics. The presented model is verified as a powerful tool for heat transfer characteristics analysis by the experimental results. With the validated models, heat transfer characteristics of the SSRC with MEMP under different operating parameters were researched and the effect of operating parameters on the heat transfer characteristics has been analyzed. All of these works can provide the basis for the later optimization design of heat transfer performance for the SSRC.